The Impact of Workload on Job Satisfaction Mediated by Employee Work Stress at the Bali Provincial Election Supervisory Agency - Pande Kadek Dwipayana Dewanta; Made Surya Putra (International Journal of Economics, Commerce, and Management, 2025)
As an institution that has a crucial role in election supervision, Bawaslu Bali Province, it is important to pay attention to employee job satisfaction can affect the quality of supervision and efficiency of the work process. Employees who have greater satisfaction with their work tend to provide healthy and positive results for the organization. The existence of problems encountered related to the satisfaction of Bawaslu Bali Province employees in working, it is necessary to identify factors that contribute to employee job satisfaction. The purpose of this study was to determine Work Stress in Mediating the Impact of Workload on Job Satisfaction of Bawaslu Bali Province Employees. This research will be conducted at the Bali Province Election Supervisory Agency. The objects of research are workload, job satisfaction, and job stress. The population in this study were 35 employees of the Bali Province Election Supervisory Agency (Bawaslu). The sample in this study used the entire population, namely 35 employees of Bawaslu Bali Province. The data collection technique used was the survey method by distributing statements given to all employees. The data analysis technique used was Partial Least Square using SmartPLS software. The results of the hypothesis testing that had been carried out obtained the results that workload had a negative effect on job satisfaction. Workload has a positive and significant effect on work stress. Work stress has a negative effect on job satisfaction. Work stress mediates the effect of workload on job satisfaction. The agency can pay attention to the balance between workload, work stress management in order to increase employee satisfaction.